Characteristics of Pulp and Paper Made from MD2 Pineapple Leaf Via Soda-Anthraquinone (AQ) Pulping Method - MOHAMAD KHALID, MOHAMAD ALIFF AFDHAL; MASROL, SHAIFUL RIZAL (Progress in Engineering Application and Technology, 2023)
Increasing demand of paper has increased the interest in searching a new alternative non-wood based raw material for papermaking industry. Pineapple leaf fibre had been utilized as one of the potential papermaking materials. Therefore, the purpose of this study is to observe the potential of pineapple leaf from Malaysian MD2 variety as papermaking fibre. MD2 pineapple leaf pulp was produced according to soda-Anthraquinone (AQ) pulping process with 20% active alkali dosage , 0.1 % AQ, 8:1 liquor to fibre ratio, 90 minutes of cooking time and 170 °C cooking temperature. Handsheet with the basis weight of 120 gsm were produced from virgin soda-AQ pulp. The characteristic test of the pulp and paper were conducted in accordance with the Technical Association of the Pulp and Paper Industry (TAPPI) and Malaysian International Organization for Standardization (MS ISO) standard. The result has observed that virgin (untreated) MD2 Soda-AQ pulp recorded a value of moisture content (76.73%), screened yield percentage (17.33%), pulp drainage time (90 s), and freeness(160ml). In physical characteristics analysis, MD2 Soda-AQ recorded a mean value of 0.522 g/cm3 and 220.545 µm for bulk density and bulk thickness, respectively. Meanwhile, mechanical characteristics also evaluated by tensile index (40.919 N.m/g), tearing index (4.588 mN.m2/g), burst index (2.734 kPa.m2/g) and folding no (12.375). This study shows the potential characteristics of MD2 pineapple leaf as a non-wood based alternative material for papermaking.